1984
DOI: 10.1002/j.1460-2075.1984.tb02053.x
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide chain elongation factor 1 alpha (EF-1 alpha) from yeast: nucleotide sequence of one of the two genes for EF-1 alpha from Saccharomyces cerevisiae.

Abstract: Messenger RNA for yeast cytosolic polypeptide chain elongation factor 1 alpha (EF‐1 alpha) was partially purified from Saccharomyces cerevisiae. Double‐stranded complementary DNA (cDNA) was synthesized and cloned in Escherichia coli with pBR327 as a vector. Recombinant plasmid carrying yEF‐1 alpha cDNA was identified by cross‐hybridization with the E. coli tufB gene and the yeast mitochondrial EF‐Tu gene (tufM) under non‐stringent conditions. A yeast gene library was then screened with the EF‐1 alpha cDNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Many of the genes coding for components of the translational apparatus are duplicated in S. cerevisiae, including TEFI and TEF2, the genes encoding elongation factor lot (EF-lat) (36,49), and EFTI and EFT2, the genes encoding EF-2 (40). The TEF3 gene was localized to the left arm of chromosome XVI, centromere distal to the RADJ gene, by hybridization of TEF3 DNA to yeast chromosomes separated by gel electrophoresis and to the library of overlapping yeast genomic DNA fragments.…”
Section: S S S L L L a I A S G A N D V S H I Q A A H V C V G I S G M mentioning
confidence: 99%
“…Many of the genes coding for components of the translational apparatus are duplicated in S. cerevisiae, including TEFI and TEF2, the genes encoding elongation factor lot (EF-lat) (36,49), and EFTI and EFT2, the genes encoding EF-2 (40). The TEF3 gene was localized to the left arm of chromosome XVI, centromere distal to the RADJ gene, by hybridization of TEF3 DNA to yeast chromosomes separated by gel electrophoresis and to the library of overlapping yeast genomic DNA fragments.…”
Section: S S S L L L a I A S G A N D V S H I Q A A H V C V G I S G M mentioning
confidence: 99%
“…It promotes the GTP-dependent binding of aminoacyl-tRNA to the ribosome and participates in the proofreading of the codon-anticodon match (16,23,38). Yeast EF-la is encoded by two unlinked genes, TEF1 and TEF2 (5,25,26,31). The two genes are efficiently transcribed at about the same level, and the presence of either gene is sufficient for cell viability and normal growth rates (4).…”
mentioning
confidence: 99%
“…The ura3-52 allele is not suppressible and does not revert (27). (26); (B) map of the TEF2-L YS2 region (31). The extent of the deletion in the tef2-A (or lys2-201) allele is also shown (31,34 confirmed that pJS7 contains one of the two genes encoding EF-la, since the 0.87-kilobase EcoRI-HindIII fragment from the pJS7 insert hybridized with the p3L6 TEF2 probe (kindly provided by C. Falco; data not shown).…”
mentioning
confidence: 99%
“…Subsequent hydrolysis of GTP and release of the factor as eEF-Tu-GDP allows its reuse throughout the elongation process (reviewed reference in 13). The functional importance of eEF-Tu in 'roteii1 synthesis has stimulated research on the structure and functional domains of the protein itself (12,29,30,33) as well as on the identification and expression of the genes for etF-Tu (2,4,14,15,19,25,31,32).…”
mentioning
confidence: 99%
“…Genomic and/or cDNA clones exist for eEF-Tu from Saccharomyces cerevisiae (4,19,25), Artemia sp. (14,31), and humans (2).…”
mentioning
confidence: 99%